Dorsomorphin attenuates Jagged1‐induced mineralization in human dental pulp cells. (9th September 2021) - Manokawinchoke, Jeeranan; Watcharawipas, Thiphon; Ekmetipunth, Kamoltham; Jiamjirachart, Manoch; Osathanon, Thanaphum
Abstract: Aim: To investigate whether TGF‐β/BMP signalling participates in Jagged1‐induced osteogenic differentiation in human dental pulp cells (hDPs). Methodology: Bioinformatic analysis of publicly available RNA sequencing data of Jagged1‐treated hDPs was performed using NetworkAnalyst. The mRNA expression was validated using real‐time polymerase chain reaction. hDPs were seeded on Jagged1 immobilized surfaces in the presence or absence of TGF‐β or BMP inhibitor. Osteogenic differentiation was evaluated using alkaline phosphatase staining, osteogenic marker gene expression and mineralization assay. Statistical analyses were performed using a Kruskal–Wallis test, followed by a pairwise comparison for more than three group comparison. Mann–Whitney U‐test was employed for two group comparison. The statistical significance was considered at p  < .05. Results: Jagged1 treatment in growth medium significantly promoted TGFB1, TGFB2 and TGFB3 whilst significantly inhibited BMP2, BMP4 and BMP6  mRNA expression ( p  < .05). In osteogenic induction medium, Jagged1 significantly up‐regulated TGFB1, TGFB2 and TGFB3 at days 1 and 3 ( p  < .05). Pre‐treatment with TGF‐β1, TGF‐β2 or TGF‐β3 prior to osteogenic induction resulted in the significant increase of osteogenic marker gene expression, collagen type 1 protein expression, alkaline phosphatase enzymatic activity and mineral deposition ( p  < .05). However, TGF‐β signalling inhibition with SB431542 (4 μmol L −1 ) or SB505124 (47 and 129 nmol L −1 ) failed to attenuate the effect of Jagged1‐induced osteogenic differentiation in hDPs. Dorsomorphin (4 and 8 μmol L −1 ) treatment significantly abolished the effect of Jagged1 on mineralization by hDPs ( p  < .05). Conclusion: Notch signalling activation by Jagged1 modulated TGF‐β and BMP ligand expression. Dorsomorphin, but not TGF‐β receptor inhibitor, attenuated Jagged1‐induced osteogenic differentiation in hDPs.